2022
DOI: 10.3390/ijerph19159219
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of DOM in the Wanggang River Flowing into the East China Sea

Abstract: Dissolved organic matter (DOM) is a central component in the biogeochemical cycles of marine and terrestrial carbon pools, and its structural features greatly impact the function and behavior of ecosystems. In this study, the Wanggang River, which is a seagoing river that passes through Yancheng City, was selected as the research object. Three-dimensional (3D) fluorescence spectral data and UV–visible spectral data were used for component identification and source analysis of DOM based on the PARAFAC model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Farmland water was the primary contributor to pollution in the Wanggang River, likely due to the significant number of farms situated along the river (Ma et al, 2022 ). Domestic sewage had a minimal impact on pollution, as it is mostly piped away from the river, resulting in low levels of untreated sewage in natural water bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Farmland water was the primary contributor to pollution in the Wanggang River, likely due to the significant number of farms situated along the river (Ma et al, 2022 ). Domestic sewage had a minimal impact on pollution, as it is mostly piped away from the river, resulting in low levels of untreated sewage in natural water bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Dissolved organic matter (DOM) plays a critical role in the breakdown of soil nutrients, as well as in the growth and metabolism of microorganisms in the field [ 55 ]. The current study found that the value of FI was greater than 1.9 under all treatments, suggesting that microbial metabolism provides the majority of DOM [ 56 ]. Moreover, the value of the BIX lower than 1 under all treatments indicated the autochthonous or biological production of DOM components sourced from terrestrial DOM [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars have successively used the EEM-PARAFAC technique to study the properties of DOM in water bodies, such as the different source characteristics of DOM in the ocean and the mechanism of DOM component changes in nearshore waters, surface sediments, permafrost, etc. [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%